Strigolactones promote flowering by inducing the miR319- LA - SFT module in tomato - Visentin, Ivan; Ferigolo, Leticia Frizzo; Russo, Giulia; Korwin Krukowski, Paolo; Capezzali, Caterina; Tarkowská, Danuše; Gresta, Francesco; Deva, Eleonora; Nogueira, Fabio Tebaldi Silveira; Schubert, Andrea; Cardinale, Francesca (Proceedings of the National Academy of Sciences - PNAS, 2024)
Strigolactones are a class of phytohormones with various functions in plant development, stress responses, and in the interaction with (micro)organisms in the rhizosphere. While their effects on vegetative development are well studied, little is known about their role in reproduction. We investigated the effects of genetic and chemical modification of strigolactone levels on the timing and intensity of flowering in tomato ( Solanum lycopersicum L.) and the molecular mechanisms underlying such effects. Results showed that strigolactone levels in the shoot, whether endogenous or exogenous, correlate inversely with the time of anthesis and directly with the number of flowers and the transcript levels of the florigen-encoding gene SINGLE FLOWER TRUSS ( SFT ) in the leaves. Transcript quantifications coupled with metabolite analyses demonstrated that strigolactones promote flowering in tomato by inducing the activation of the microRNA319- LANCEOLATE module in leaves. This, in turn, decreases gibberellin content and increases the transcription of SFT . Several other floral markers and morpho-anatomical features of developmental progression are induced in the apical meristems upon treatment with strigolactones, affecting floral transition and, more markedly, flower development. Thus, strigolactones promote meristem maturation and flower development via the induction of SFT both before and after floral transition, and their effects are blocked in plants expressing a miR319-resistant version of LANCEOLATE . Our study positions strigolactones in the context of the flowering regulation network in a model crop species.